Beginning of Protection of Children’s Rights in the Vietnamese Legal Development - HUYNH THI TRUC , Giang (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
In Vietnam, the government has focused on protecting children’s rights for many years, especially after the State signed the United Nations Convention on the Rights of the Child; however, whether such rights existed during the French colonial rule in Vietnam is an issue that needs to be clarified. This paper is formulated on the premise that the protection of children’s right was legislated in the Vietnamese law during the French occupation. In order to prove this position, this paper considers the laws enforced during the French colonial rule in Vietnam (1858–1945).